Assessment of Heavy metals in Water, Sediment and Fishes of the Baleh River, Sarawak, Malaysia - Chai, Hui Ping (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Pollution of heavy metals in aquatic environment is a subject of concern as rivers play an important role to the local inhabitants for various daily activities. The objective of the study is to determine the distribution and contamination status of heavy metals (Al, Cr, Cu, Mn, Ni, Zn, Fe, As, Se, Hg) in water, sediment and fishes of the Baleh River. Water and sediment samples were collected from 50 stations and 22 fish species were caught for metal analysis. For water, acid extractable metals were determined and only Al was found higher than the drinking water guideline due to enhanced surface runoff. Dissolved and total metal contents in 10 stations were compared with the acid extractable metals. The concentration of total metals were significantly higher than the dissolved and acid-extractable metals. The contamination status of sediment was evaluated using the geochemical indices with the baseline concentrations determined based on the cumulative distribution curves. The assessment suggested low contamination risk in sediment. For fishes, metals tend to be accumulated in gills, except Hg which was found higher in muscle. The metal concentration in muscle was compared against Malaysia Food Act; Al was detected at a concentration exceeding the permissible level for most species possibly due to the elevated Al concentration in water. Hg was found in higher concentrations in carnivorous and bottom feeders due to their feeding habits. The hazard index calculated was greater than 1 for some species suggesting possible adverse health effects where the consumption limits was between 143.54 g and 716.80 g per week. Overall, the study concluded low contamination risk in water and sediment of the Baleh River, with fish species demonstrating potential Al and Hg accumulation where continuous monitoring is recommended.